Clinical case of Bloch - Sulzberger syndrome - Nadezhda V. Krasnova; Tatyana A. Chernova; Irina V. Alekseeva; Geliya G. Gimalieva; Tatiana Misyakova; Larisa G. Sinitsyna (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Purpose.To present a clinical case of Bloch Sulzberger syndrome. Material and methods. The examinations were performed to diagnose the disease: а visual examination of the skin, cytological analysis of the gallbladder fluid, general and biochemical blood tests, genetic research. Results.During a visual examination of the skin, a differential diagnosis was made with infectious dermatitis, toxic-allergic dermatitis, epidermolysis bullosa and linear IgA-dependent dermatosis in children. Crucial in the diagnosis belonged to a genetic study, after which a deletion of exons 410 of the IKBKG gene was detected, which confirmed Bloch Sulzberger syndrome. Conclusion.Newborns with vesicle-bullous rashes entering the neonatal pathology department and observed by neonatologists require a thorough examination, a mandatory consultation of a dermatologist inorder to determine further management tactics.